Orthophoto Map as Supporting Data for Urban Development Management - Taryono, Taryono (Forum Geografi, 1997)
System and management of urban development, whih its concept is environmental outlands, is hughly depended on the accuracy of data and information. To comply with the deamnd it is neede the availability of integrated urban information which is loaded by relevance, validity, reliability, and timely. The information mode meant, includes 1) information dimension of spatial unit; 2) identification of user information k.e: who needsÂ the information and on what stage the information shall be used; 3) identification of information requirement of every stage developer; 4) AMDAL of the developed urban area. Input of data and information are achieved by remote sensing on orthophoto as the outcoming of this activity are geometrical and semantical data.